Improving infrastructure or lowering taxes to attract foreign direct investment? - Christian Bellak; Markus Leibrecht (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2009)
This Perspective compares the impact of improving infrastructure versus lowering taxes on attracting and keeping FDI and discusses the policy implications for countries seeking to attract FDI, especially countries currently debating the relative merits of cutting taxes versus increased spending.
Keywords: 330